(untitled) (Journal of Surgical Sciences, 2026)
Background: Recent concept of enteral nutrition provision with good outcome gradually changes the current practice of postoperative management. But commercially available enteral formula is often costly, not affordable by native people, and often not tolerable. This study was carried out to compare the effect of total parenteral nutrition (TPN) versus early enteral nutrition (EEN) on postoperative outcomes and nutrition related cost after pancreatoduodenectomy. Methods: Thirty patients who underwent pancreatoduodenectomy within one year in the Department of Hepatobiliary, Pancreatic & Liver Transplant Surgery, BSMMU included and categorized into two groups; EEN(n=15) group: enteral feeding made with indigenous food and TPN (n=15) group: only parenteral nutrition continued up to six/seven post-operative days (POD). In all the patients, biochemical parameter was measured on POD 1, 3, 7 & 14 for assessing primary end point (Nutritional condition, morbidity and mortality) and secondary end point (length of postoperative hospital stays, albumin requirement and nutrition related cost). Results: EEN was shown to have a significant effect on reducing the overall complications rate (3/15 vs 10/15, p<0.01s) and infectious complications rate (2/15 vs 7/15, p<0.04s) compared with TPN. Additionally, EEN saved average 23 thousand taka (270 dollars) in costs compared to TPN for postoperative nutrition purpose. There were significant differences between TPN and EEN groups regarding mean duration of nutrition in EEN group 5.27±0.59 and in TPN group 9.73±4.28 days, time to start solid food (8.20±1.01 vs 12.87±4.50 days,p<0.001s),albumin requirement (1.47±0.99 vs 3.40±1.68 unit, p<o.oo1s), Inflammatory parameter and electrolyte imbalance (hypokalemic episode) significantly reduced at postoperative day 3 and day 7 in EEN group compare to TPN with less antibiotic and electrolyte support. Length of hospital stay is significantly longer in TPN in contrast to EEN (15.27±6.41 vs 10.47±2.10 days, p=0.001). There were no significant differences between TPN and EEN groups regarding mortality rate. Conclusion: Blended meals prepared from locally available food may be considered as an alternate to commercially available enteral feeding formula after pancreatoduodenectomy. It reduces morbidity, electrolyte imbalance, albumin requirement and nutritional cost. Thus, ensure smooth postoperative recovery than TPN. Journal of Surgical Sciences (2023) Vol. 27 (1) : 11-17